Video analysis of anterior cruciate ligament injury - Boden, B. P.; Torg, J. S.; Knowles, S. B.; Hewett, T. E. (The American Journal of Sports Medicine, 2009)
Most anterior cruciate ligament research is limited to variables at the knee joint and is performed in the laboratory setting, often with subjects postinjury. There is a paucity of information on the position of the hip and ankle during noncontact anterior cruciate ligament injury.